Family Nursing Care Using The PIS-PK Approach (Healthy Indonesia Program-Family Approach) As an Effort To Increase The Healthy Family Index - Wulandari, Ning Arti; Romadhon, Wimar Anugrah; Abiddin, Andi Hayyun (STIKes Patria Husada Blitar, 2024)
Health development focuses on preventive activities by increasing awareness and the ability to live healthily for everyone in order to improve the level of public health. Health development should start from the smallest unit of society, namely the family. One of the government policies to achieve health development in Indonesia is PIS-PK (Healthy Indonesia Program-Family Approach). The PIS-PK program is very much in line with the concept of family nursing care, which is a nursing practice activity with a family nursing process approach. The aim of this activity was to increase the Healthy Family Index after providing family nursing care. The target of this activity was 10 families suffering from non-communicable diseases in RT.03/RW.02, Tanjungsari Village, Blitar City. The methods used start from assessment activities, establishing nursing diagnoses, determining nursing interventions, implementing nursing and conducting evaluations. This form of activity involved home visits to all target families. The indicators of success of this activity were the achievement of all nursing outcomes determined in the process of implementing nursing care and an increase in the healthy family index. The data obtained was presented in descriptive form. The results of this activity were an increase in the Healthy Family Index, of the 6 families in the Pre-Healthy category after being given family nursing care, 4 of them increased to healthy families and all the nursing outcomes specified in nursing care were all fulfilled. It is suggested to community health center nurses to apply this family nursing care in implementing the PIS-PK program.